Indução da ovulação em novilhas com PGF2α - Leonardi, Carlos Eduardo Porciuncula (2011)
In this study the effect of exogenous 500μg cloprostenol sódico (PGF2α Ciosin®) with or without previous intravaginal progesterone (P4) releasing insert (CIDR) treatment on the ovulation rate of prepubertal heifers was evaluate. Forty crossbred Angus prepubertal heifers 250 kg in average were randomly assigned into three experimental groups: Progesterone + PGF2α Group (PPG Group, n = 12) plus an im. injection of PGF2α at the CIDR s remove, PGF2α Group (PG Group, n = 14) heifers were treated im with PGF2α five days after follicular wave emergence and the Control Group (n = 14) were not treated. Immediately after CIDR insert, the PPG heifers received im 50 mg of progesterone and 2 mg of estradiol benzoate. The CIDRs were removed on the fifth day after the emergence of a new follicular wave. The rate of ovulation was higher in PPG (10/12; 83.33%) and PG Groups (11/14; 78.50%) than in the Control Group (1 / 14; 7.14%) (P < 0.0001). Our study indicates that PGF2α induces ovulation in prepubertal heifers in spite of its use with or without exogenous progesterone.